DoE-based Optimization of Oral In-situ Gel containing Dandelion Leaf Extract - Dholakia, Mansi; Patel, Dinal V.; Chauhan, Harshida; Suhagia, Bhanubhai N. (Drug Delivery Letters, 2022)
Aim: The present study developed an oral in-situ gel containing the leaf extract of Taraxacum officinale (T.O.) using an experimental design. Background: Peptic ulcer disease was an epidemic in the 19th and early 20th centuries. The application of herbal drugs for peptic diseases is an attractive area for research and implementation as compared to the allopathic system in the recent era. From the number of plants, the antioxidant effect of an aqueous extract of Taraxacum officinale, which is the dandelion leaf, was proven by an animal study in previous literature. However, most of the marketed preparations consist of root extract primarily used for the detoxification of the liver in comparison to the leaf extract having a nonspecific application. Hence, the aqueous extract of dandelion leaf was taken as the active ingredient in the formulation. Over the past 30 years, greater attention has been given to the development of controlled and sustained drug delivery systems. The development of in situ gel systems has received considerable attention over the past few years due to the number of advantages. Objective: By considering the merits of herbal ingredients with drug delivery technology, herbal in-situ gel was developed using statistical analysis. Methods: Herbal in-situ oral gel was developed using a factorial design. The concentration of sodium alginate, xanthan gum, and HPMC K15 M was taken as the factors, and viscosity and drug release (total phenol content) in 10 h were selected as the responses. By evaluating the designed batches, the optimized batch was chosen as the promising formulation for curing the peptic ulcer. Results: The batch consisting of 1.711% w/v sodium alginate, 0.727% w/v xanthan gum, and 0.869% w/v HPMC K15M was selected as the optimized batch, as per the software, and the viscosity and % drug release in 10 h were found to be 299.5 cps and 70.2%, respectively. Other evaluation parameters such as gelling capacity, floating parameters, and stability were also found to be good for the designed batches. Conclusion: The improved in-situ gel was found to be effective for extending the floating of the drug incorporated into the formulation as well as the residence time in the stomach for sustained drug release.
Keywords: peptic ulcer